Pengaruh Stres Kerja, Kepuasan Kerja Dan Komitmen Organisasi Terhadap Kinerja Pegawai: Pada Dinas Pemuda Dan Olahraga Kabupaten Jayapura - Sokoy, Raymond; Kambuaya, Balthasar; Risamasu, Ferdinand (Magister Manajemen Universitas Cenderawasih, 2025)
This study aims to: (1) analyze the simultaneous effects of work stress, job satisfaction, and organizational commitment on employee performance at the Youth and Sports Office of Jayapura Regency; (2) examine the partial effects of these variables on employee performance; and (3) identify the most dominant variable influencing employee performance. The study population consists of all employees of the Youth and Sports Office of Jayapura Regency, totaling 26 individuals, with a sample of 23 employees. A multiple regression analysis was employed to test the significance of the relationships between work stress, job satisfaction, organizational commitment, and employee performance, given the correlational nature of the hypotheses. The findings indicate that work stress, job satisfaction, and organizational commitment significantly influence employee performance when analyzed simultaneously. Partially, work stress negatively affects employee performance, where lower levels of work stress are associated with higher performance. Job satisfaction exhibits a positive relationship with employee performance, suggesting that higher job satisfaction enhances performance. Similarly, organizational commitment positively influences employee performance, with highly committed employees demonstrating better performance. Among these three variables, job satisfaction exerts the most dominant influence on employee performance, highlighting its crucial role in determining employees' performance levels within the organization.